International journal of politics. ([White Plains, N.Y.], [International Arts and Sciences Press], 1971)
Contains translations of material that has appeared originally in scholarly journals, books, and legal documents throughout the world.
"A journal of translations."
Also issued online.
SERBIB/SERLOC merged record
Keywords: Political science -- Periodicals; Science politique -- Périodiques.; Political science; Political science -- Periodicals; Periodicals; Periodicals